REGULASI HORMONAL TERHADAP KOMPETENSI DAN PENENTUAN MORFOLOGI BUNGA: TELAAH LITERATUR TENTANG PERAN GIBBERELLIN DAN SITOKININ - Retno Utari; Wan Syafi'i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Flower development is a complex physiological process regulated by internal hormonal signals that determine meristem competence and the morphological identity of floral organs. This literature review synthesizes research findings related to the roles of gibberellin (GA) and cytokinin (CK) in the regulation of floral competence and the determination of flower morphology. The review method involved selecting relevant scientific articles from national journals using keywords associated with gibberellin, cytokinin, floral induction, floral meristem, and floral organ development. The analyzed studies indicate that GA plays a significant role in the transition from the vegetative to generative phase by modulating the expression of genes associated with flowering induction, as well as influencing internode elongation and floral organ identity. Meanwhile, CK contributes to promoting cell division, enhancing meristematic activity, and stimulating the initiation of floral primordia. Several findings also highlight the importance of GA–CK interactions in maintaining hormonal balance that governs the timing, structure, and developmental success of flowers. This review provides a comprehensive understanding of hormonal mechanisms in flower development and serves as a reference for further research in plant physiological regulation.